The Influence of Product Quality on Customer Loyalty in Bumma Food Business, Makassar City - Muhammad Rafli; Andi Mustika Amin; Muhammad Ilham Wardhana Haeruddin; Siti Hasbiah; Muh. Ichwan Musa (International Humanity Advance, Business & Sciences, 2023)
This study aims to determine the effect of product quality on customer loyalty in the Bumma Food Makassar City business. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study with a sample size of 100 people. The data were analyzed using a simple regression analysis method with the help of SPSS data processing to prove the hypothesis. The results showed that the product quality variable had a positive and significant effect on customer loyalty. This means that the better and more quality the products offered at Bumma Food Makassar city to customers will be able to create customer loyalty for the products offered.